Bill Cunningham : on the street : five decades of iconic photography - Cunningham, Bill, 1929-2016 (Clarkson Potter/Publishers, 2019)
"This official book of photographs houses the 50-year collection of the most iconic and beloved photographs taken by prolific fashion photographer Bill Cunningham, the King of Street Style. The iconic Bill Cunningham was known for wearing a blue work jacket and riding a bicycle around New York City as he captured cutting-edge street style (before street style was even a thing). He took pictures for The New York Times from 1978 until his death in 2016 and wrote the beloved columns "On the Street" and "Evening Hours," which began in 1989. This book will be an oversized collection of Bill's hallowed photography--a mixture of published and unpublished--organized by decade with essays by and about Bill's muses and subjects like Anna Wintour, Cathy Horyn, Vanessa Friedman, and Ruth La Ferla. Every fashion lover and fashionista--from NYC and beyond--will have to add this book to their collection"--